View-specific effects of depth rotation and foreshortening on the initial recognition and priming of familiar objects - Lawson, Rebecca; Humphreys, Glyn W. (Perception & psychophysics, 1998)
In a series of three experiments, we examined, first, the effects of viewpoint in depth on the efficiency of initial picture naming and, second, the effects of priming on subsequent naming. On initial presentation, foreshortened views were harder to name than were more typical (nonforeshortened) views. In addition, priming increased as a function of the similarity of the prime and target. Indeed, if a foreshortened view of an object had already been named, the subjects named a subsequent foreshortened view of that object as fast as or faster than they named a subsequent, more typical view. These results provide evidence against theories that predict full view-invariant object recognition and view-invariant priming of object recognition. Instead, the results support theories that suggest that object recognition is mediated by stored representations that are both view- and object-specific.